Pendampingan Penerapan Sertifikasi Halal Produk UMKM dalam Meningkatkan Daya Saing - Wenny Surya Murtius; Prima Fithri; Cesar Welya Refdi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Activities intended for Micro, Small and Medium Enterprises (MSMEs) in West Sumatra in obtaining Halal product certificates. The activity began with socialization and registration by MSMEs for products to be registered for halal certification. MSMEs, which are generally engaged in food processing, lack knowledge of the importance of product legality. The need to obtain product certification is demanded by increasing market competition and public awareness of the importance of the safety of a product they consume. In addition, the lack of knowledge of small business actors about the procedures that must be passed is also a significant problem. So, the implementation of this activity is significant in increasing the competitiveness of partner products. This community engagement activity aimed to help partners in product and business development and become partner facilitators to obtain product Halal certificates.